Pathways, Challenges and Strategies for Enhancing Teachers’ Digital Literacy in the Context of Educational Digitalisation - Wang, Mengqi (Journal of Educational Research and Policies, 2025)
This study examines teacher digital literacy within the context of educational digitalisation. It first establishes that educational digitalisation represents an inevitable trend, with teacher digital literacy being pivotal to the success of this transformation, thereby underscoring the study’s theoretical and practical significance. The paper then defines the concept of teacher digital literacy, elaborating on its framework through five dimensions: digital awareness, digital knowledge and skills, digital application, digital social responsibility, and professional development. It then discusses practical pathways for enhancing teachers’ digital literacy, including establishing tiered and categorised training models, integrating and expanding training resources, and developing shared digital teaching resources. The paper also identifies challenges such as insufficient technological application capabilities and lagging educational philosophy updates. Consequently, it proposes enhancement strategies including self-directed learning and self-improvement, improving in-school training and incentive mechanisms, regional resource sharing and collaborative development, and government policy guidance and financial support.